2002
DOI: 10.1042/bj20020189
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen induction of a novel fatty acid n−6 desaturase in the soil protozoon, Acanthamoeba castellanii

Abstract: Induction of fatty acid desaturation is very important for the temperature adaptation of poikilotherms. However, in oxygen-limited late-exponential-phase Acanthamoebacastellanii cultures, oxygen alone was able to induce increased activity of a fatty acid desaturase that converts oleate into linoleate and which has been implicated in the temperature adaptation of this organism. Experiments with Δ10-nonadecenoate showed that the enzyme is an n-6 desaturase rather than a Δ12-desaturase. It also used preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…On investigation, we found that oxygen availability (independent of temperature) could regulate the de novo synthesis of oleate desaturase protein [44,45]. We also found that oxygen availability could limit the activity of pre‐existing oleate desaturase in A. castellanii [45].…”
Section: Acanthamoeba Castellanii – a Simple Animal Systemmentioning
confidence: 84%
“…On investigation, we found that oxygen availability (independent of temperature) could regulate the de novo synthesis of oleate desaturase protein [44,45]. We also found that oxygen availability could limit the activity of pre‐existing oleate desaturase in A. castellanii [45].…”
Section: Acanthamoeba Castellanii – a Simple Animal Systemmentioning
confidence: 84%
“…; Rutter et al. ). Other studies have shown that LA and OA are the most active uncouplers and protonophores in A. castellanii mitochondria (Swida et al.…”
Section: Discussionmentioning
confidence: 98%
“…This may be because A. castellanii used the excess OA to synthesize a range of polyunsaturated fatty acids (Rutter et al. ) catalyzed by the fatty acid n‐6 desaturase; or used OA as a substrate to esterify phospholipids through catalysis by Δ12,Δ15‐desaturase (Sayanova et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations